The Role of Corporate Governance Practices on Saudi Stock Exchange Voluntary Disclosure - Barnawi, Maher Hamzah M; Abdullah, Dewi Fariha; Fuzi, Nursyazwani Mohd (Advances in Social Sciences Research Journal, 2024)
This study examines the impact of corporate governance practices on voluntary disclosure among non-financial firms listed on the Saudi Stock Exchange (Tadawul) from 2011 to 2022. The research focuses on key governance variables, including board size, board independence, CEO duality, audit committee effectiveness, ownership structure, and board diversity, to understand their influence on transparency and information sharing. Employing panel data analysis, the study utilizes fixed effects, random effects, and pooled OLS models, with the fixed effects model emerging as the most robust. The findings reveal that board size, board independence, audit committee effectiveness, ownership structure, and board diversity significantly enhance voluntary disclosure, whereas CEO duality and firm-specific factors such as firm age and leverage show limited influence. The results highlight the importance of strong corporate governance frameworks in fostering transparency and aligning with Saudi Arabia’s Vision 2030 goals to attract foreign investment and boost market confidence. This study contributes to the literature on corporate governance and disclosure in emerging markets, offering practical insights for policymakers and corporate leaders to improve governance structures and reporting practices.